N and P Retranslocation Efficiency in Three Evergreen Tree Species Planted in Two Different Habitats of Varying Fertility Status - Singh, Arvind (Indian Forester, 2007)
Nitrogen and phosphorus retranslocation efficiencies were measured in three evergreen tree species planted on mine spoil and the efficiencies were compared with same aged plants of same species planted on normal soil. The N and P retranslocation efficiencies were found greater in plants planted on mine spoil in all three tree species compared to those planted on soil. The two non-leguminous species Eucalyptus hybrid and Grevillea pteridifolia had shown a higher efficiency for N retranslocation and lower efficiency for P retranslocation, while contrary to this the only legume L. leucocephala had shown a higher efficiency for P retranslocation and a lower efficiency for N retranslocation.